Patterns of prevalent HPV and STI co-infections and associated factors among HIV-negative young Western Cape, South African women: the EVRI trial. (10th May 2017) - Menezes, Lynette J; Pokharel, Ubin; Sudenga, Staci L; Botha, Matthys H; Zeier, Michele; Abrahamsen, Martha E; Glashoff, Richard H; Engelbrecht, Susan; Schim van der Loeff, Maarten F; van der Laan, Louvina E; Kipping, Siegfried; Taylor, Douglas; et al.
Abstract : Objective: To estimate the prevalence and describe the patterns of concurrent human papillomavirus (HPV) and STIs and associated factors among HIV-negative young Western Cape, South African women participating in the Efficacy of HPV Vaccine to Reduce HIV Infection (EVRI) trial. Methods: HIV-negative women aged 16–24 years old were enrolled in the EVRI trial (NCT01489527 ) and randomised to receive the licensed four-valent HPV vaccine or placebo. At study entry, participants were clinically evaluated for five STIs: herpes simplex virus type 2 (HSV-2), chlamydia, gonorrhoea, syphilis and disease-causing HPV genotypes (6/11/16/18/31/33/35/39/45/51/52/56/58/59/68). Demographic and sexual history characteristics were compared among women with STI co-infections, single infection and no infection using Pearson χ 2 and Mann-Whitney tests. ORs were calculated to evaluate factors associated with STI co-infection prevalence. Results: Among 388 young women, STI co-infection prevalence was high: 47% had ≥2 concurrent STIs, 36% had a single STI and 17% had none of the five evaluated STIs. HPV/HSV-2 (26%) was the most prevalent co-infection detected followed by HPV/HSV-2/ Chlamydia trachomatis (CT) (17%) and HPV/CT (15%). Co-infection prevalence was independently associated with alcohol use (adjusted OR=2.01, 95% CI 1.00 to 4.06) and having a sexual partner with an STI (adjusted OR=6.96, 95% CI 1.53 to 30.08). Conclusions: Among high-risk young women from underserved communities such as in Southern Africa, a multicomponent prevention strategy that integrates medical and behavioural interventions targeting both men and women is essential to prevent acquisition of concurrent STI infections and consequent disease. Trial registration number: NCT01489527 ; Post-results.